The Strip-Ground Rectangular Patch Antenna - Yiying Wang; Yinghua Lu (International Journal of Antennas and Propagation)
To imitate the broken situation of the conductive threads of the wearable antenna, a strip-ground design of rectangular patch antenna with the conventional substrate is presented to investigate the change of the antenna performance, where the ground is sliced along its E-plane. The strips are symmetrical along the center line of the width of the patch, and the gap ratio of the gap to the solid ground varies with the change of gaps. The conventional patch antenna is used as a reference for comparison with the stripe-ground antennas. And the effect of the coaxial cable, the changes of the impedance, and the cross-polarization of the antenna are investigated. Several antenna prototypes are fabricated and their measured results are in good agreement with the simulations. These results show that the gaps change the performance of the strip-ground antennas, but they can work well if the gap ratio is less than 1 : 4.